Pengaruh E-Service Quality Terhadap E-loyalty dengan Brand Image dan E-Satisfcation Sebagai Variabel Mediasi - Saputro, Anggoro Wisnu; Utomo, Hadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to analyze the effect of e-service quality on e-loyalty with brand image and e-satisfaction as mediating variables for student customers using Livin' by Mandiri mobile banking in Sleman Regency. The sampling technique uses a non-probability sampling technique with purposive sampling. Data was obtained using a questionnaire technique in the form of a Google form which was distributed online to 100 respondents. The data analysis method in this study used the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the Smart PLS 4.0 data processing program. The results of this study indicate that e-service quality has a positive and significant effect on e-loyalty, e-service quality has a positive and significant effect on brand image, e-service quality has a positive and significant effect on e-satisfaction, brand image has a positive and significant on e-loyalty, electronic e-satisfaction has a positive and significant effect on e-loyalty, brand image mediates the effect of e-service quality on e-loyalty, e-satisfaction mediates the effect of e-service quality on e-loyalty.